The effect of fibrin extracellular matrix properties for the in vitro angiogenesis assay - Ishak, Siti Amirah (2015)
Angiogenesis, the formation of new vascular network from the pre-existing vasculature, has been studied in the connection to the normal developmental process as well as numerous diseases. In tissue engineering research, angiogenesis is also essential to promote micro-vascular network inside engineered tissue constructs, mimicking a functional blood vessel in vivo. Besides, the formation of new blood vessels depends strongly on the extracellular matrix such as fibrin gel. In this study, we investigate the effect of four different ratio of fibrinogen (mg/mL) to thrombin (Units/mL) composition (i.e., 2:1, 1:2, 1:8, 8:1), on the physical properties of fibrin gel and the role of fibrin gel for angiogenesis assay with HSF. Some properties of fibrin gel such as clotting time, water uptake property, turbidity and microstructure observation was studied. Higher concentration of thrombin (i.e., 8:1 mg/U) will yields a shorter clotting time of the fibrin gel when compared to the lower concentration of thrombin (i.e 1:8 mg/U). Fibrin gel with higher thrombin and lower fibrinogen concentration (i.e., 1:8 mg/U) are not stable enough to withstand the amount of PBS subjected to it hence it cannot absorb water well compared to other fibrin gel concentration. Meanwhile, at higher concentration of thrombin, the turbidity study shows the lowest absorbance compared to other samples. Different ratio of fibrinogen to thrombin may affect the microstructure of the fibrin gel produced. Microstructure observation proved that fibrin gel produced in this study shows the fibrous structure. The last part of this experiment also proved that fibrin gel with ratio of 2:1 mg/U of fibrinogen to thrombin reveal the best tube-like structure which has the highest number of nucleus as well as highest number of tube-like structure formed after 48 hours.